Peranan Personal Selling Dalam Usaha Meningkatkan Penjualan Pada PT âXYZâ - Supariyani, Emmy (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2002)
Mixture of marketing constitutes one of effective marketing strategies to increase selling. The role of personal selling conducted by PT XYZ could be known based on how far the influence of personal selling to the escalation of selling and how personal selling conducted by firm got effectiveness and achieved determinate targets. In this research itâs an assumption that factors out of promotion activity didnât shift.